PTU-012 A novel submucosal injection solution: data on safety and efficacy from a large prospective EMR series. (23rd September 2015) - Longcroft-Wheaton, G R; Mead, R; Bhandari, P
Abstract : Introduction: Submucosal injection is an integral part of EMR. The ideal solution will produce a long lasting high elevation, and an avascular field with delineation of tissue planes. This requires a combination of various drugs and solutions. However, no such mix is commercially available. This has resulted in a wide range of mix being used in this country, with no data on the safety, efficacy and long-term results of these solutions. We have developed an ideal mix of gelofusine (colloid) to provide a long lasting lift with adrenaline to reduce the vascularity of the field and indigo carmine to adequately delineate tissue planes. We aim to illustrate the feasibility, safety and efficacy and long-term effects of our novel submucosal lifting solution. Methods: The lifting solution was: 500 mls gelofusine, 2 mls 1:1000 adrenaline and 5 mls indigocarmine 0.4%. We reviewed all EMRs since 2005. Records were assessed to collect data on efficacy of the solution, immediate and late mucosal and systemic effects. Data were collected on type and size of lesions, procedure time and volume of solution used. Results: A total of 546 lesions were removed. 411 polypectomies and 135 upper GI EMRs. Volume used was between 5-250 mls, dependent on lesion size and procedure time (range 20 min–180 min). Distribution of upper GI lesions: 99 oesophageal EMRs, 20 gastric EMRs and 16 duodenal EMRs. Endoscopic follow-up data were available on 107 cases, with a mean interval of 3 months (range: 2–6 months). There was no evidence of immediate or late complications, including tissue injury, necrosis or stenosis related to the solution. For the lower GI lesions: 411 polyps removed. There were 143 polyps >2 cm in size. Left sided lesions=121 (median 45 mm range 20–150), right sided lesions=22 (median 31 mm, range 20–50). Procedure time 20 min–180 min. There were follow-up data on 117 colonic EMRs, with a mean interval of 4 months (range 0.5–60 months). There was no evidence of any late complications, including tissue injury necrosis or stenosis at the previous polypectomy sites. The endoscopist found the solution extremely effective and provided good lift after one injection in all of the cases examined. There was a short lived 5–20% rise in pulse rate. There were no immediate cardiac complications preventing completion of the procedures. No anaphylaxis or allergic reaction. There was no local or systemic sepsis related to the solution. No obvious renal or hepatic effects reported. Conclusion: Largest reported series on submucosal injection solution in the world; Have clearly demonstrated the feasibility and efficacy of this novel injection mix; Shows immediate and long-term safety of this solution; Shows some systemic effects like tachycardia so caution is advised in cardiac patients.